Evaluation of non-volatile taste components in commercial soy sauces. Issue 1 (1st January 2018) - Kong, Yan; Zhang, Li-Li; Zhang, Yu-Yu; Sun, Bao-Guo; Sun, Ying; Zhao, Jing; Chen, Hai-Tao
ABSTRACT: The dominating non-volatile taste compounds in commercial brewed soy sauces were determined by HPLC and evaluated on the contributions to overall taste. Aspartic acid and glutamic acid accounted for 8.77 to 147.98 mg/mL in ten commercial soy sauces samples. Lactic acid (ranging from 0.83 to 13.19 mg/mL) and pyroglutamic acid (ranging from 0 to 12.80 mg/mL) were the dominant organic acids, contributing to the acidity and ensuring a balance in taste of soy sauces. 5ʹ-Inosine monophosphate was the most abundant nucleotide, followed by 5ʹ-guanosine monophosphate, and they accounted for 0.30 to 3.54 mg/mL in ten soy sauces. According to the determination of non-volatile taste compounds in soy sauce samples, taste activity value (TAV) and equivalent umami concentration (EUC) of different soy sauces were calculated and compared. An exclusive cluster analysis based on TAV was proposed to classify the commercial soy sauces. The EUC value of new class A is much higher than other classes.